Participatory learning to raise rural women’s agency: Cultivating leadership and advocacy in Nigeria - Kyle, Jordan; Adeyanju, Dolapo; Carrillo, Lucia; Efem-Bassey, Vivian; Kosec, Katrina; Olanrewaju, Opeyemi; Anisimova, Evgeniya (International Food Policy Research Institute, 2023)
Women in rural areas often do not have equal opportunities in labor markets and face challenges in accessing land, credit, insurance, technology, and agricultural resources. Barriers such as unpaid care work, limited skills training, regressive gender norms, and gender-based violence further limit their ability to increase or diversify income. Another possible, and often overlooked, barrier is a lack of women’s voice and agency in both private and public spaces.